Digital Cyclical Ecological Regional Self-Sufficient Economy - Bryndin , Evgeniy (Journal of Applied Science, Engineering, Technology, and Education, 2020)
The economy is sphere of public work and the set of relations that form in the system of production, distribution, exchange and consumption. The paper examines the digital, cyclical, environmental and regional aspects of a cyclical digital environmental regional economy. The digital direction of the economy uses digital twins and robots as assistants to improve its quality, productivity and efficiency. The cyclical economy uses savings and profits to boost its competition and development. The environmental direction of the economy maintains the viability of the environment. The regional economy increases diversification and capacity of local production and preserves the environment in its territory regardless of the type of economic activity. Cyclical aspects of the economy of self-sufficiency mainly concern the financial round-up, and the closed reproduction cycle. Business models of cyclic reproduction realize its economic self-sufficiency. At present, Russia, China, the United States and EU integration education have achieved the optimal level of national economic self-sufficiency. Russia, the United States, and the EU have the necessary financial and human resources. At the same time, China, with excessive human resources, is pursuing a policy of expansion into developing and underdeveloped countries. The main reason for countries to abandon autarky policies in favor of globalization of research activities is the decline in profit levels. The reason for this situation lies in the availability of cheap labour and favourable economic conditions, and production in countries is therefore cheaper. The reason for globalization and the international division of labour lies in maximizing profits, and autarks in maximizing national production, i.e. self-sufficiency. The unity of the Autarky State must be ensured by the existence of economic, historical, cultural ties, as well as by national equilibrium.